2010
DOI: 10.1080/09541440802708136
|View full text |Cite
|
Sign up to set email alerts
|

From melody to lexical tone: Musical ability enhances specific aspects of foreign language perception

Abstract: Previous research shows that music ability provides positive effects on language processing. This study aims at better clarifying the involvement of different linguistic subdomains in this cross-domain link, assessing whether or not musicality and music expertise enhance phonological and lexical tone processing of Mandarin Chinese. In two experiments different groups of adults and children with no previous experience in tonal languages, were invited to perform a same-different task trying to detect phonologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
85
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 20 publications
13
85
2
Order By: Relevance
“…Secondly, musical experience has a beneficial impact on the processing of phoneme duration and overall language segmentation (see Table 2). Marie et al (2011), in contrast to Delogu et al (2010), showed that musical training enhanced discrimination and categorization of both segmental and tonal contrasts. In a cross-linguistic study, Sadakata and Sekiyama (2011) compared musicians and non-musicians and found that musical expertise benefited discrimination of speech materials more than identification in both L1 and L2, and the greatest effect of musicality on identification processes was seen in the temporal aspects of speech (duration of consonants and vowels).…”
Section: Enhanced Phonological Processing and Production And L2 Comprmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, musical experience has a beneficial impact on the processing of phoneme duration and overall language segmentation (see Table 2). Marie et al (2011), in contrast to Delogu et al (2010), showed that musical training enhanced discrimination and categorization of both segmental and tonal contrasts. In a cross-linguistic study, Sadakata and Sekiyama (2011) compared musicians and non-musicians and found that musical expertise benefited discrimination of speech materials more than identification in both L1 and L2, and the greatest effect of musicality on identification processes was seen in the temporal aspects of speech (duration of consonants and vowels).…”
Section: Enhanced Phonological Processing and Production And L2 Comprmentioning
confidence: 99%
“…Delogu et al (2010) and Marie et al (2011) also suggest that the positive effect of music expertise on enhanced perceptual processing might arise because musicians rely on both left-lateralized segmental cue processing and right-lateralized tonal cue processing. Therefore, weaker brain lateralization and enhanced subcortical processing, induced by musical activities, could play a role in learning L2 that is very different from the native one.…”
Section: Notementioning
confidence: 99%
“…On top of enhanced processing pertaining to pitch, musicians are found to be more sensitive to timbre than non-musicians (Chartrand and Belin, 2006), an acoustic property assumed to contribute to voice quality and emotion in speech (Juslin and Laukka, 2003). Meanwhile, musicians are also reported to outperform non-musicians in other language tasks such as second language production and perception, pitch memory, verbal memory, and perhaps segmental processing (Bidelman et al, 2013;Chan et al, 1998;Slevc and Miyake, 2006;Marie et al, 2011; although see Delogu et al, 2010). In the current study, the talker identification task in each language condition involved five different talkers and was cognitively more complex than pitch perception.…”
Section: A the Impact Of Musical Training On Pitch And Talker Identimentioning
confidence: 99%
“…Putting pitch use in the musical domain aside, in speech, pitch can be used linguistically to contrast word meanings or sentence type, or used paralinguistically to denote speakers' emotions or identity. It is well documented that musicians excel at detecting subtle pitch changes in lexical tones (Delogu et al, 2010) and are sensitive to pitch contours that differentiate a statement from a question (e.g., Deguchi et al, 2012) as do tone language speakers (e.g., Stevens et al, 2013). Moreover, suggestive evidence exists showing a relationship between individual differences in pitch processing on speech and non-speech tasks, indicating that the use of pitch in linguistic and non-linguistic domains relies on overlapping resources (Perrachione et al, 2013).…”
Section: Shared Mechanisms: Music Language and Voice Perceptionmentioning
confidence: 99%
See 1 more Smart Citation